(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
Siganus rivulatus, a Lessepsian migrant fish species, has successfully colonized the southern Mediterranean Sea. This study aimed to investigate the morphometric characteristics of S. rivulatus from Soussa coast, eastern Libya, southern Mediterranean Sea. Twenty specimens were measured individually for fourteen morphometric parameters. The mean length and weight of the fish were 19.52 cm and 109.35 g, respectively. Pairwise correlations among the morphometric parameters were highly significant, ranging from strong to moderate positive relationships. Regression analyses revealed that all parameters increased at different rates with fish length and head length. Fulton’s condition factor (KF) of 1.44 and Clark’s condition factor (KC) of 1.16 indicated that the fish were in good health. The ’b’ value of the power regression for the length-weight relationship of 2.93 suggests slightly negative allometric growth.